2015
DOI: 10.1016/j.virol.2014.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress influences positive strand RNA virus genome synthesis and capping

Abstract: Flaviviruses are 5′ capped positive-stranded RNA viruses that replicate their genomes within endoplasmic reticulum-derived vesicles. Flaviviruses are well known to induce oxidative stress late in infection but it is unknown if oxidative stress plays a positive role in the viral RNA replication cycle. We therefore examined how oxidation affects flavivirus RNA replication. We found that antioxidant treatment reduced virus production, reduced the viral positive-to-negative strand RNA ratio, and resulted in the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 56 publications
3
75
0
Order By: Relevance
“…The increased expression of the ISE6 proteins observed on infection with LGTV may reflect a generalized cellular response or metabolic processes and products used by the virus [4]. Flaviviruses are thought to exploit the cellular stress response to aid replication [51] and oxidative stress is thought to aid the replication of positive-strand RNA viruses [52]. Further, it has been proposed that the balance between antioxidant responses maintains an anti-apoptotic environment during flavivirus infection of the cell [53, 54], presumably facilitating virus replication and transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of the ISE6 proteins observed on infection with LGTV may reflect a generalized cellular response or metabolic processes and products used by the virus [4]. Flaviviruses are thought to exploit the cellular stress response to aid replication [51] and oxidative stress is thought to aid the replication of positive-strand RNA viruses [52]. Further, it has been proposed that the balance between antioxidant responses maintains an anti-apoptotic environment during flavivirus infection of the cell [53, 54], presumably facilitating virus replication and transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of flaviviruses, it was shown that the guanylyltransferase activity of NS5 encoded polymerase was enhanced by oxidative conditions. 61 It remains to be determined if there are specific aspects of mitochondrial dysfunction that may be controlled by antioxidant treatment, which may have important implications in protecting terminally differentiated neurons in the infected host. Our follow up hypothesis was that mitochondrial fission may contribute to the ensuing apoptosis in infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…AdoHcy thus plays a crucial role in the interplay between the nsP1 functions, probably not by competition with AdoMet for the MTase inhibition but rather by inducing conformational changes favoring the GT reaction. During the preparation of the manuscript, Gullberg and coworkers showed that AdoMet and consequently AdoHcy are not necessary to produce the m 7 GMP-nsP1 product (58). However, the study was performed in the presence of GTP-ATTO 680, a GTP analog whose modification in position 8 could possibly affect the chemical properties of GTP and favor the guanylylation reaction.…”
Section: Discussionmentioning
confidence: 99%